2017
DOI: 10.1002/ece3.3399
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐facilitated effects of exotic earthwormPontoscolex corethruruson the soil carbon and nitrogen dynamics and soil microbial community in a subtropical field ecosystem

Abstract: Earthworms and plants greatly affect belowground properties; however, their combined effects are more attractive based on the ecosystem scale in the field condition. To address this point, we manipulated earthworms (exotic endogeic species Pontoscolex corethrurus) and plants (living plants [native tree species Evodia lepta] and artificial plants) to investigate their combined effects on soil microorganisms, soil nutrients, and soil respiration in a subtropical forest. The manipulation of artificial plants aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The epigeic E. fetida also enhanced organic N mineralisation in the rhizosphere of Phormium tenax, a New Zealand lilaceous perennial (Zhong et al, 2017). The overall positive effect of earthworms on C and N mineralisation in the rhizosphere was shown by Wu et al (2017) who demonstrated that P. corethrurus affected C and N processes and the soil microbial community in plots where living plants were present, in contrast to plots where artificial plants were used as controls.…”
Section: Earthworms Increase Nutrient Mineralisation In the Soilmentioning
confidence: 97%
See 1 more Smart Citation
“…The epigeic E. fetida also enhanced organic N mineralisation in the rhizosphere of Phormium tenax, a New Zealand lilaceous perennial (Zhong et al, 2017). The overall positive effect of earthworms on C and N mineralisation in the rhizosphere was shown by Wu et al (2017) who demonstrated that P. corethrurus affected C and N processes and the soil microbial community in plots where living plants were present, in contrast to plots where artificial plants were used as controls.…”
Section: Earthworms Increase Nutrient Mineralisation In the Soilmentioning
confidence: 97%
“…Some authors, however, did not detect any earthworm effect on potentially mineralisable N (Fonte and Six, 2010) or, on the contrary, evidenced a decrease in N mineralisation by earthworms (Groffman et al, 2015), most likely due to an increase in microbial immobilisation that caused total soil N to decrease by 90 g N m −2 in presence of the epigeic L. rubellus. A possible explanation which has been proposed by several authors is that N mineralised by earthworms and their associated microorganisms might be used more readily by plants, thereby masking an increase in soil available N concentrations (Pashanasi et al, 1996;González and Zou, 1999;Wu et al, 2017). Similarly, the amount of readily available phosphorus (P) has been shown to be affected by earthworms, levels of available P being higher in casts (Jiménez et al, 2003;Kuczak et al, 2006;Vos et al, 2014;Ros et al, 2017) or in biopores formed by L. terrestris (Athmann et al, 2017) than in the bulk soil.…”
Section: Earthworms Increase Nutrient Mineralisation In the Soilmentioning
confidence: 99%
“…Fungus-earthworm interactions cover an array of direct and indirect mechanisms including arbuscular mycorrhizal fungi (AMF), so fungus-plant interactions (Paudel et al, 2016;Wang et al, 2021;Zaller et al, 2011), and the breakdown of organic matter and consequences for soil fertility (Aira et al, 2008;G omez-Brand on et al, 2011;Haitoa et al, 2018;Wu et al, 2017). Earthworm-fungus interactions are generally positive (G omez-Brand on et al, 2012), with the composting activity of epigeic earthworms increasing fungal mass (Aira et al, 2006(Aira et al, , 2008Chauhan, 2014;G omez-Brand on et al, 2011;Haitoa et al, 2018;Lazcano et al, 2008;Sharma et al, 2017;Srivastava et al, 2011;Wu et al, 2017) and earthworms grazing on fungi (Cooke, 1983;Moody et al, 1995), potentially increasing growth (Kaushik et al, 2012). While digestion of ingested fungal spores has been noted (Schönholzer et al, 1999), egested material has also been reported to leave fungi unaffected (G omez-Brand on et al, 2011;Pedersen & Hendriksen, 1993), and earthworms could therefore assist fungal dispersal.…”
Section: Fungi and Earthwormsmentioning
confidence: 99%
“…Because, by bioturbation, earthworms stabilize organic matter in soil, form soil aggregates, modify the structure and chemical composition of soil [29]. Such changes generally increase soil water holding capacity, soil nutrient content, and plant productivity [28][29][30]. Most previous studies justified this better enhancement of acacia growth performance in the presence of earthworm by the fact that in metal-contaminated soil, some earthworms species (Eisenia fetida, Lumbricus terrestris, P. corethrurus) can decrease the content of potential toxic elements (PTEs) in metal contaminated soil through the accumulation potential toxic elements (PTEs) in their tissues and consequently promote plant growth [31][32][33].…”
Section: Plant Growth Performance Under Different Treatmentsmentioning
confidence: 99%